Cross-Media Strategy of Networked Private Local Television: A Case Study of SMTV Sumedang in the Digital Era - Pipit Nurvina; Aryo Subarkah Eddyono (Communicatus: Jurnal Ilmu komunikasi, 2026)
The advancement of digital technology has compelled the media industry to adapt to shifting audience consumption patterns. Local television faces significant challenges due to the emergence of digital media and internet-based platforms. Despite growing scholarly attention to media convergence, existing studies focus primarily on single-platform transitions and fail to address the structural dynamics of network-affiliated private stations, leaving a gap regarding how such stations sustain relevance within national network structures while preserving local identity. This study examines the cross-media strategy adopted by SMTV, a private local television station affiliated with the Jawa Pos network, in navigating the media digitalization era. Employing a qualitative case study method through in-depth interviews with seven key informants, eight months of participatory observation, and documentation analysis, the findings reveal three specific outcomes: (1) SMTV positions itself at the cross-promotion and cloning stages of Dailey et al.’s (2005) convergence continuum, anchored by a TV-first production paradigm; (2) content is repurposed across YouTube, Instagram, and TikTok with platform-specific format adaptation, with initial indications toward integrated storytelling; and (3) three structural constraints, limited financial capital, network-affiliation content guidelines, and regulatory disparities, create a convergence ceiling preventing progression toward full convergence. Theoretically, the findings extend the convergence continuum framework by demonstrating that structural, regulatory, and network-affiliation factors significantly shape convergence trajectories in peripheral media markets of the Global South, challenging the assumption that convergence progression is primarily a function of organizational willingness.